Marula [Sclerocarya birrea (A. Rich.) Hochst.] products as a food and medicine - Olas, Beata (Frontiers in Pharmacology, 2025)
The fruit of Sclerocarya birrea (A. Rich.) Hochst., commonly known as the marula, is widely appreciated for its nutritious pulp and edible nuts. The pulp has a higher vitamin C than those of other fruits, including pineapple, guava, and oranges. In addition, fresh marula fruits are often used to produce delicious sweets, wine and flavorings: it is perhaps best known as the flavor of Amarula liqueur. In vitro and in vivo studies indicate that the various parts of marula have pro-health properties, such as antioxidant, antibacterial, antifungal, antidiabetic activities. This paper reviews the current state of knowledge regarding the marula fruit and its products, with a special emphasis on their chemical composition, biological activity and pro-health potential.